Archeologia dei paesaggi e approcci cognitivi: strumenti GIS e sistemi teorici di analisi spaziale a confronto con documentazione archeologica di antico stampo - Marco Anzalone; Daniele Alaimo (Archeomatica, 2017)
Our study focuses on Morgantina and the surrounding area, from the Bronze Age until the fourth century A.D., a study motivated by lack informations about an area so rich in history and archaeological evidences, not all investigated. Our research is characterized by the attempt to use GIS tools and theoretical systems of spatial analysis, usually adopted by modern geographical science; instruments that we tried to use for an ancient geography's reconstruction, having a so lacking and antiquated archaeological documentation: our intent it's not predictive, but it's a verification of the results of this approach opposite to an incomplete and messy archaeological record.